Early prehistoric navigation in the Western Mediterranean: Implications for the Neolithic transition in Iberia and the Maghreb - Zilhão, João (2018)
Early Neolithic sea voyaging and organized colonization of large islands involving crossings in the range of 100 km are well documented in the Eastern and Central Mediterranean. In the west, the distribution of obsidian from Tyrrhenian sources and the lack of human settlement in the Balearic archipelago until later prehistoric times suggest a pattern of contact, exchange and dispersal where navigation would have been restricted to small-scale, in-sight-of-land crossings and cabotage journeys. For the spread of farming into Iberia to have followed a North African route, the path of entry must therefore have been the Straits of Gibraltar, which presupposes an earlier emergence of the Neolithic in the Maghreb, where the associated impressed ware material culture in turn implies an ultimate origin in southern Italy and, therefore, the crossing of the Siculo-Tunisian Strait. In North Africa, however, the earliest directly dated domesticates post‑date by several centuries similar evidence from Valencia, Andalucía and Portugal, while the presence of Pantelleria obsidian in the nearest mainlands substantiates prehistoric navigation between Europe and Africa in the central Mediterranean after ~7000 cal BP, only at a time when farming economies were already several centuries old in Iberia. The material culture similarities perceived in the Early Neolithic of southern Iberia and the Maghreb may indicate a North‑to‑South diffusion of farming across the Straits of Gibraltar but not the reverse.